Water Consumption by Chir Pine (Pinus roxburghii). Banj-oak (Quercus incana), Sal (Shorea robusta) and IPIL-IPIL (Leucaena leucocephala) in Juvenile Stage - Raturi, A. S.; Dabral, B. G. (Indian Forester, 1986)
The paper details the water consumption behaviour or Chir-pine, Banj-Oak, Sal and Ipil-Ipil in Juvenile stage conducted in plastic and glazed earthen pots. Amongst Chir-pine, Oak and Sal, lowest transpiration ratio is depicted by Chir-pine and the highest by Oak. Although the transpiration ratio of Ipil-Ipil is lowest, its water consumption is highest. Ipil-Ipil being a rast growing species requires bigger space than that provided here for conducting the experiment. The results indicate that due to the comparatively bigger needs for water consumption by Chir-pine, replacement of degraded Oak forests by this species, on the northern aspects may dry the sites adversely, affecting the water regime of the tract but on southern and western aspects which are comparatively warmer and dryer the water regime may not be significantly affected. Thus it is thought that such degraded Oak areas in the hills, earmarked for Oak regeneration, should not be brought under Chir-pine, lest the already deficit soil moisture regime may further deteriorate. Besides, pines have a tendency to turn alkaline soils acidic, which is detrimental for Oak regeneration. However, studies are required to be done on the watersheds itself for confirmation. The plastic pots seem better indicative of treatment responses compared to the glazed earthen pots.